2020
DOI: 10.2139/ssrn.3738629
|View full text |Cite
|
Sign up to set email alerts
|

Application of Text Mining to the Analysis of Climate-Related Disclosures

Abstract: The Working Paper Series seeks to disseminate original research in economics and fi nance. All papers have been anonymously refereed. By publishing these papers, the Banco de España aims to contribute to economic analysis and, in particular, to knowledge of the Spanish economy and its international environment.The opinions and analyses in the Working Paper Series are the responsibility of the authors and, therefore, do not necessarily coincide with those of the Banco de España or the Eurosystem.The Banco de Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
3
8
0
Order By: Relevance
“…Our analysis also shows massive reporting gaps in the description of targets used by the bank to manage climaterelated risks and opportunities and the performance against these targets. Demaria and Rigot (2020) and Moreno and Caminero (2020) yielded similar results. Demaria and Rigot (2020) suggested that reporting on quantified emission limitation targets over different time horizons needs improvement.…”
Section: Metrics and Targetssupporting
confidence: 59%
See 2 more Smart Citations
“…Our analysis also shows massive reporting gaps in the description of targets used by the bank to manage climaterelated risks and opportunities and the performance against these targets. Demaria and Rigot (2020) and Moreno and Caminero (2020) yielded similar results. Demaria and Rigot (2020) suggested that reporting on quantified emission limitation targets over different time horizons needs improvement.…”
Section: Metrics and Targetssupporting
confidence: 59%
“…We were also able to identify some reporting gaps in our analysis. In the Metrics and Targets category, banks seemed to find it difficult to formulate (science-based) targets and report performance against these targets (Moreno & Caminero, 2020). However, further investigation showed that participants in the SBTi had statistically higher reporting quality, especially for the issue mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already recently highlighted by a report published by the Spanish Central Bank [46], "The multiplicity of standards and recommendations and the fact that there is still no XBRL taxonomy for ESG reporting, which would make this data computer-readable, means that analysts have to go through usually lengthy pdf documents to extract the key information they require for their analysis, whether it is for supervisory, credit assessment, investment or other purposes". According to the authors, this situation usually results in ESG disclosure provided in a separate document, non-XBRL compliant.…”
Section: Current Taxonomymentioning
confidence: 99%
“…First of all, there is a lack of standardization of the disclosures, which is important due to its impact on the banks’ performance indicators. Disclosures were found general, providing no further useful information, infrequent, annual disclosures were repetitive and symbolic [ 11 ], there is an imbalance among some disclosure categories and lack of standardization due to data scarcity [ 12 ]. Furthermore, disclosures in their prescriptive nature do not provide an adequate risk picture as they are predominantly backwards-looking.…”
Section: Literature Reviewmentioning
confidence: 99%